Motivation and Behaviour of Thai Outbound Tourists to Europe / Witchu Chaipinit and Kullada Phetvaroon - Chaipinit, Witchu; Phetvaroon, Kullada (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2011)
This study uses motivation and behavior theory to understand and explore the characteristics of Thai outbound tourists who are traveling to Europe. It was conducted using 400 questionnaires with Thai tourists who were waiting for flights to travel to Europe at Suvarnabhumi International Airport. The behaviors of the outbound tourists are described using the following four classifications: tourists' travel patterns, tourists' behavior before traveling, behavior during the trip and the important considerations affecting traveling behavior. This paper also offers an integrated approach to understanding Thai outbound tourist's motivation and attempts to extend the empirical knowledge on the outbound tourist's push and pull motivations. These motivations are observed with 15 push factors and 20 pull factors. The results of the study show that Thais travelling to Europe are divided almost equally between male and female in terms of quantity. The largest group oftravelers consists of tourists between 30 and 39 years of age and they are most often government officials. The majority of respondents have traveled abroad I to 3 times. 70% of the respondents used travel agents to arrange their trips and 81.5% of respondents planned to stay in Europe for 1 to 3 weeks and 84.7% preferred to stay in 3 to 4-star accommodation. In relation to financial factors, outbound tourists are most concerned about airfares and accommodation. They are most concerned with the high cost associated with traveling and potential language problems. The most influential motivating factor in deciding to travel was reported as the desire to discover new places and learn about new cultures and lifestyles.